2014
DOI: 10.1007/s10926-014-9519-4
|View full text |Cite
|
Sign up to set email alerts
|

Factors Related to Participation in Paid Work After Organ Transplantation: Perceptions of Kidney Transplant Recipients

Abstract: The ability to return to paid work after kidney transplant is a complex phenomenon, likely impacted by a combination of person- and work-related factors, which contributed to how individuals perceived their abilities to attain or return to paid work. It is important that in facilitating renal transplant recipients to resume valued life occupations such as paid work, the dynamic interactions between personals values, perception of one's abilities, skills, job requirements and employer characteristics be conside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
52
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(62 citation statements)
references
References 29 publications
8
52
2
Order By: Relevance
“…We found less kidney transplanted patients working post-Tx than before, a finding in agreement with Nour et al [16] and Tzvetanov et al [23], but in opposition to a recent Swiss study [9] that reported more kidney transplanted patients working post-Tx (71%) than before. The latter study is a retrospective monocentric survey with a response rate of 55% and may, therefore, have overestimated employment status due to a possible selection bias.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…We found less kidney transplanted patients working post-Tx than before, a finding in agreement with Nour et al [16] and Tzvetanov et al [23], but in opposition to a recent Swiss study [9] that reported more kidney transplanted patients working post-Tx (71%) than before. The latter study is a retrospective monocentric survey with a response rate of 55% and may, therefore, have overestimated employment status due to a possible selection bias.…”
Section: Discussionsupporting
confidence: 90%
“…Comparable results were found in reports from the US [11] and from Belgium [22] with 56% and 58% employed post-Tx, respectively. Compared to other studies, the post-Tx employment rate is high [14, 16, 17, 23, 24]. This is mostly due to an already high employment rate of 58.9% pre-Tx in our cohort.…”
Section: Discussioncontrasting
confidence: 69%
See 3 more Smart Citations